ESTÉTICA Y POLÍTICA EN EL PERIODO CHILENO DE MARIANO PICÓN SALAS (1923-1935). - Antzus Ramos, Ioannis (Revista Chilena de Literatura, 2018)
In this article I study the aesthetic thought and the relations between aesthetics and politics in the essays that Mariano Picon Salas wrote in Chile between 1923 and 1935. In his texts on art, the young Picon Salas valued authentic and harmonious works in which the meaning and the signifier as well as the creator and the context established an unambiguous relation. At the same time, in what concerns his political thought, Picon longed for an agreement between the elites and the people that would lead to overcome the institutional and social crisis and to undertake the road of modernization.